Iron Bioavailability Studies of the First Generation of Iron-Biofortified Beans Released in Rwanda - Glahn, Raymond P.; Tako, Elad; Hart, Jonathan J.; Haas, Jere D.; Lung'aho, Mercy G.; Beebe, Stephen E. (MDPI, 2017)
This paper represents a series of in vitro iron (Fe) bioavailability experiments, Fe content analysis and polyphenolic profile of the first generation of Fe biofortified beans (Phaseolus vulgaris) selected for human trials in Rwanda and released to farmers of that region. The objective of the present study was to demonstrate how the Caco-2 cell bioassay for Fe bioavailability can be utilized to assess the nutritional quality of Fe in such varieties and how they may interact with diets and meal plans of experimental studies. Furthermore, experiments were also conducted to directly compare this in vitro approach with specific human absorption studies of these Fe biofortified beans. The results show that other foods consumed with beans, such as rice, can negatively affect Fe bioavailability whereas potato may enhance the Fe absorption when consumed with beans. The results also suggest that the extrinsic labelling approach to measuring human Fe absorption can be flawed and thus provide misleading information. Overall, the results provide evidence that the Caco-2 cell bioassay represents an effective approach to evaluate the nutritional quality of Fe-biofortified beans, both separate from and within a targeted diet or meal plan.